2015
DOI: 10.1016/j.atherosclerosis.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

HIV and coronary arterial remodeling from the Multicenter AIDS Cohort Study (MACS)

Abstract: Objective Positive remodeling (PR), a coronary artery characteristic associated with risk for myocardial infarction (MI), may be more prevalent in HIV-infected (HIV+) people. We evaluated the prevalence of PR using coronary CT angiography (CCTA) in HIV+ and HIV-uninfected (HIV−) men. Methods/Results Men enrolled in the Multicenter AIDS Cohort Study underwent CCTA if they were 40–70 years, had normal kidney function and no history of coronary revascularization. Multivariable logistic regression models were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Asymptomatic HIV-infected persons also have an increased prevalence of subclinical atherosclerosis with more calcified and, particularly more noncalcified coronary artery plaque compared with HIV-uninfected individuals (14). In addition, HIV-infected persons appear to have a higher prevalence of vulnerable plaque that is associated with increased risk of CVD events (29).…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic HIV-infected persons also have an increased prevalence of subclinical atherosclerosis with more calcified and, particularly more noncalcified coronary artery plaque compared with HIV-uninfected individuals (14). In addition, HIV-infected persons appear to have a higher prevalence of vulnerable plaque that is associated with increased risk of CVD events (29).…”
Section: Discussionmentioning
confidence: 99%
“…Activated immune cells also contribute to plaque remodeling, promoting the development of high-risk morphology plaque features which predispose to atherothrombosis(8). In studies focused on MLHIV, systemic markers of monocyte activation have been related to arterial inflammation(9, 10), subclinical carotid and coronary artery atherosclerosis(1114), and pathologically remodeled coronary atherosclerotic plaque(15, 16). Studies focused predominantly on WLHIV have revealed relationships between systemic immune markers and carotid atherosclerosis(1719), as well as the percent of non-calcified coronary atherosclerotic plaque(6).…”
Section: Systemic Immune Activation/ Inflammation and Hiv-associated mentioning
confidence: 99%
“…Activated immune cells (particularly monocytes-turned-macrophages, but also T cells and other types of immune cells) participate meaningfully in atherosclerotic plaque formation and pathologic plaque remodeling(20). Several physiology studies performed in all-male or predominantly male (>90% male) cohorts have revealed relationships between systemic markers of monocyte activation (sCD163, sCD14) and surrogates of atherosclerotic cardiovascular disease (ASCVD) risk including subclinical carotid artery atherosclerosis(21), aortic inflammation(22) (23), subclinical coronary atherosclerotic plaque(24) (25) (26), and pathologically remodeled coronary atherosclerotic plaque(27) (28). Separate physiology studies among WLHIV have confirmed parallel relationships between systemic immune activation markers and ASCVD risk surrogates, including subclinical carotid atherosclerosis(29) (30) (31) and the percent of non-calcified coronary atherosclerotic plaque(32).…”
Section: Sex-specific Mechanisms Underlying Heightened Cvd Risk Amongmentioning
confidence: 99%